Non-stick pan coating and preparation method thereof
By using tannin-modified chitin-derived carbon and nano-silicon carbide in the non-stick pan coating to form a thermal conductivity network, the problem of insufficient thermal conductivity of the non-stick pan coating in the prior art is solved, and better thermal conductivity, uniform heat dissipation and wear resistance are achieved, while maintaining non-stick properties.
Patent Information
- Application Number
- CN202311067066.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-08-23
AI Technical Summary
After adding aluminum powder or silicon carbide filler in the existing non-stick pan coating, the thermal conductivity of the existing non-stick pan coating is still difficult to achieve the expected effect, and excessive addition will reduce the non-stick performance.
Tannic acid-modified chitin-derived carbon and nanosilicon carbide are used to form a thermal conductivity network through tannin acid, and are fully dispersed in fluorine-containing resin and ethanol to form a non-stick pot coating.
It improves the thermal conductivity and uniform heat dissipation performance of the non-stick pan coating, while maintaining the non-stick performance and enhancing the wear resistance.
Smart Images

Figure BDA0004409814260000061 
Figure BDA0004409814260000071 
Figure BDA0004409814260000072
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of non-stick pans, and in particular to a non-stick pan coating and a preparation method thereof. Background Art
[0002] A non-stick pan is a pan that does not stick to the bottom of the pan when cooking. The reason is that the bottom of the pan is coated with a non-stick coating. Common non-stick coatings include Teflon coatings and ceramic coatings. Among them, the main components of Teflon coatings are organic substances such as polytetrafluoroethylene and polyvinylidene fluoride. The low surface tension characteristics of organic substances such as polytetrafluoroethylene and polyvinylidene fluoride make it difficult for solids to adhere to the surface of organic substances such as polytetrafluoroethylene and polyvinylidene fluoride.
[0003] However, since organic substances such as polytetrafluoroethylene and polyvinylidene fluoride have poor thermal conductivity, in order to maintain the heat during cooking, fillers such as aluminum powder, silicon carbide, etc. are often added to organic substances such as polytetrafluoroethylene and polyvinylidene fluoride to improve the thermal conductivity of non-stick pans.
[0004] In actual operation, excessive addition of aluminum powder, silicon carbide and other substances will reduce the non-stick performance of the Teflon coating. In order to ensure the non-stick performance of the non-stick pan, the addition of aluminum powder, silicon carbide and other substances is small, making it difficult for the Teflon coating to achieve the expected thermal conductivity effect. Summary of the invention
[0005] In order to solve the problem in the prior art that the thermal conductivity of non-stick pan coatings still fails to achieve the expected effect after adding aluminum powder, silicon carbide and other substances to organic substances such as polytetrafluoroethylene and polyvinylidene fluoride, the present application provides a non-stick pan coating and a preparation method thereof.
[0006] In a first aspect, the present application provides a non-stick pan coating, which adopts the following technical solution:
[0007] A non-stick pan coating comprises the following components by weight: 120-160 parts of fluorine-containing resin, 9-24 parts of chitosan-derived carbon modified by tannic acid, 3-8 parts of nano silicon carbide, and 80-120 parts of ethanol.
[0008] By adopting the above technical scheme, the chitosan-derived carbon has excellent thermal conductivity, and after being modified by tannic acid, the chitosan-derived carbon can be fully dissolved in fluorine-containing resin and ethanol; nano-silicon carbide also has excellent thermal conductivity, and the catechol and pyrogallol structures on the tannic acid are adsorbed on the nano-silicon carbide through π-π interaction, so that the chitosan-derived carbon modified by tannic acid and the nano-silicon carbide form a thermal conductive network, which provides a fast channel for phonon transmission and improves the thermal conductivity and uniform heat dissipation performance of the non-stick pan coating; and the chitosan-derived carbon and nano-silicon carbide modified by tannic acid account for a small proportion in the non-stick pan coating, thereby having little effect on the performance of the fluorine-containing resin, so that the non-stick performance of the non-stick pan can still be effectively maintained; in addition, the chitosan-derived carbon and nano-silicon carbide have excellent wear resistance, and the chitosan-derived carbon and nano-silicon carbide are dispersed as evenly as possible in the fluorine-containing resin and ethanol through tannic acid, thereby improving the wear resistance of the non-stick pan coating.
[0009] Preferably, the method for preparing the chitosan-derived carbon modified by tannic acid comprises the following steps:
[0010] (1) Carbonization and degassing: chitosan is placed in a tube furnace, the temperature is raised from room temperature to 400-1000°C under a nitrogen atmosphere, then naturally cooled to room temperature and degassed under vacuum conditions for 4-6 hours to obtain chitosan-derived carbon;
[0011] (2) Dispersion: placing the chitosan-derived carbon in deionized water and ultrasonicating for 4-6 hours to obtain a dispersion;
[0012] (3) Modification: adding Tris to the dispersion and mixing evenly, adjusting the pH to 8-9 with HCl solution, adding tannic acid, mixing evenly and reacting to obtain a modified solution;
[0013] (4) Centrifugal drying: centrifuge the modified solution, discard the supernatant, add deionized water to the precipitate, centrifuge for multiple times and discard the supernatant until the pH of the supernatant is 7.0, remove the supernatant, collect the precipitate and dry it to obtain the modified powder.
[0014] By adopting the above technical scheme, chitosan is carbonized and degassed in a tubular furnace to generate chitosan-derived carbon with excellent thermal conductivity, and the aggregation degree of chitosan-derived carbon in deionized water is reduced by ultrasonic dispersion; in a Tris-HCl buffer solution, tannic acid is oxidatively self-polymerized and coated on the surface of chitosan-derived carbon to complete the modification of chitosan-derived carbon; finally, impurities are removed by centrifugation, and the powder of the dried or modified chitosan-derived carbon is obtained.
[0015] Preferably, in step (1), the temperature of the tube furnace is increased to 700-900°C.
[0016] By adopting the above technical scheme, if the temperature of the tubular furnace is too high, the thermal conductivity of the chitosan-derived carbon will decrease, and the oxygen-containing functional groups of chitosan will produce a large amount of gas escape during the carbonization process, so that the generated chitosan-derived carbon will generate a porous structure. When the temperature is too high, the pore structure may collapse, which is not conducive to phonon transmission; if the temperature of the tubular furnace is too low, the thermal conductivity of the chitosan-derived carbon is low, and the pore structure generated during the carbonization of chitosan is small, making it difficult for phonons to be fully transmitted in the chitosan-derived carbon, so that the thermal conductivity of the non-stick pan coating is difficult to meet the expected requirements; for this reason, the applicant finally determined that the temperature of the tubular furnace in the present application is more preferably the above result after a lot of research and experimental verification.
[0017] Preferably, in step (3), the weight ratio of the chitosan-derived carbon to tannic acid is 6:1-3.
[0018] By adopting the above technical scheme, if the tannic acid content is small, it is difficult for tannic acid to fully modify the chitosan-derived carbon, and the thermal conductive network formed by the modified chitosan-derived carbon and nano-silicon carbide is relatively sparse, making it difficult for the thermal conductivity of the non-stick pan coating to meet the expected requirements; if the tannic acid content is high, tannic acid has already fully modified the chitosan-derived carbon, and from the perspective of material cost, there is no need to continue to increase the tannic acid content; for this reason, the applicant finally determined, after a lot of research and experimental verification, that the weight ratio of chitosan-derived carbon to tannic acid in the present application is preferably the above.
[0019] Preferably, in step (3), the reaction time of the chitosan-derived carbon and the tannic acid is 3-6 hours.
[0020] By adopting the above technical scheme, if the reaction time of chitosan-derived carbon and tannic acid is short, it is difficult for tannic acid to fully modify the chitosan-derived carbon, and the thermal conductive network formed by the modified chitosan-derived carbon and nano-silicon carbide is sparse, making it difficult for the thermal conductivity of the non-stick pan coating to meet the expected requirements; if the reaction time of chitosan-derived carbon and tannic acid is short, tannic acid has completed the full modification of chitosan-derived carbon, and from the perspective of production cost, there is no need to continue to increase the reaction time; for this reason, the applicant finally determined after a lot of research and experimental verification that the reaction time of chitosan-derived carbon and tannic acid in this application is preferably the above.
[0021] Preferably, the weight ratio of the chitosan-derived carbon modified with tannic acid to the nano-silicon carbide is 3-4:1.
[0022] By adopting the above technical scheme, if the proportion of chitosan derived carbon modified by tannic acid is relatively large relative to nano-silicon carbide, a large amount of tannic acid can only adsorb a small amount of nano-silicon carbide, so that the thermal conductive network formed by the modified chitosan derived carbon and nano-silicon carbide is relatively sparse, making it difficult for the thermal conductivity of the non-stick pan coating to meet the expected requirements; if the proportion of chitosan derived carbon modified by tannic acid is relatively small relative to nano-silicon carbide, the tannic acid content is limited, the adsorbed nano-silicon carbide has reached saturation, and the thermal conductive network formed by the modified chitosan derived carbon and nano-silicon carbide is relatively dense, so that the thermal conductivity of the non-stick pan coating meets the requirements, and continuing to increase the amount of nano-silicon carbide not only increases the material cost, but also may affect the non-stick performance of the non-stick pan coating; for this reason, the applicant finally determined after a lot of research and experimental verification that the weight ratio of chitosan derived carbon modified by tannic acid to nano-silicon carbide in this application is preferably as above.
[0023] In a second aspect, the present application provides a method for preparing a non-stick pan, using the following technical solution:
[0024] A method for preparing a non-stick pan coating comprises the following steps:
[0025] (1) substrate treatment: the non-stick pan substrate is subjected to sandblasting roughening treatment to obtain an uneven inner surface of the non-stick pan substrate, and then the inner surface of the non-stick pan substrate is degreased and cleaned to obtain a treated non-stick pan substrate;
[0026] (2) Preliminary stirring: weighing the chitosan-derived carbon modified with tannic acid, nano-silicon carbide and ethanol according to weight, and stirring and mixing for a certain period of time to obtain a mixed solution;
[0027] (3) Stirring and spraying: adding the mixed solution to the fluorine-containing resin, stirring and mixing for a certain period of time, and then spraying and granulating to obtain a powder with a particle size of 1-10 μm;
[0028] (4) Preparing a coating: placing the treated non-stick pan substrate in a vacuum chamber, evacuating the chamber and introducing nitrogen, and then spraying the powder onto the inner surface of the treated non-stick pan substrate by plasma spraying to obtain a non-stick pan coating.
[0029] By adopting the above technical scheme, the chitosan derived carbon modified by tannic acid, nano-silicon carbide and ethanol are first stirred and mixed, so that the chitosan derived carbon modified by tannic acid and nano-silicon carbide are first fully dispersed in the ethanol and form a thermal conductive network; then the mixed liquid is added to the fluorine-containing resin, so that the chitosan derived carbon modified by tannic acid and nano-silicon carbide are more fully dispersed, thereby ensuring that the prepared non-stick pan coating has sufficient thermal conductivity.
[0030] Preferably, in step (2), stirring is required at 1000-2000 rpm for 1-2 hours.
[0031] By adopting the above technical scheme, if the stirring rate in step (2) is low and the stirring time is short, the chitosan-derived carbon modified by tannic acid and nano-silicon carbide are easily stacked together, so that the thermal conductive network cannot be fully dispersed in the non-stick pan coating, thereby reducing the thermal conductivity of the non-stick pan coating; if the stirring rate in step (2) is high and the stirring time is long, the thermal conductive network formed by the chitosan-derived carbon modified by tannic acid and nano-silicon carbide has been fully dispersed in the non-stick pan coating, thereby ensuring the thermal conductivity of the non-stick pan coating. From the perspective of production cost, there is no need to continue to increase the stirring rate and stirring time; for this reason, the applicant finally determined, after a lot of research and experimental verification, that the stirring rate and stirring time in step (2) of the present application are preferably the above.
[0032] Preferably, in step (3), stirring is required at 1000-2000 rpm for 1-2 hours.
[0033] By adopting the above technical scheme, if the stirring rate in step (3) is low and the stirring time is short, the chitosan-derived carbon modified by tannic acid and nano-silicon carbide are easily stacked together, so that the thermal conductive network cannot be fully dispersed in the non-stick pan coating, thereby reducing the thermal conductivity of the non-stick pan coating; if the stirring rate in step (3) is high and the stirring time is long, the thermal conductive network formed by the chitosan-derived carbon modified by tannic acid and nano-silicon carbide has been fully dispersed in the non-stick pan coating, thereby ensuring the thermal conductivity of the non-stick pan coating. From the perspective of production cost, there is no need to continue to increase the stirring rate and stirring time; for this reason, the applicant finally determined, after a lot of research and experimental verification, that the stirring rate and stirring time in step (3) of the present application are preferably as above.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. Since the present application uses tannic acid-modified chitosan-derived carbon and nano-silicon carbide to form a thermal conductive network through tannic acid and is evenly dispersed in the non-stick pan coating, the non-stick pan coating has excellent thermal conductivity; and the tannic acid-modified chitosan-derived carbon and nano-silicon carbide account for a relatively small proportion in the non-stick pan coating, thereby having little effect on the performance of the fluorine-containing resin, so that the non-stick performance of the non-stick pan can still be effectively maintained; in addition, the non-stick pan coating also has excellent uniform heat dissipation performance and wear resistance; 2. When preparing the non-stick pan coating in the present application, the tannic acid-modified chitosan-derived carbon, nano-silicon carbide and ethanol are first stirred and mixed, and then the obtained mixture is added to the fluorine-containing resin, so that the non-stick pan coating obtained thereby ensures sufficient thermal conductivity, uniform heat dissipation and wear resistance. DETAILED DESCRIPTION
[0036] The non-stick pan coating provided by the present application comprises the following components in parts by weight: 120-160 parts of fluorine-containing resin, 9-24 parts of chitosan-derived carbon modified by tannic acid, 3-8 parts of nano silicon carbide, and 80-120 parts of ethanol.
[0037] The fluorine-containing resin can be adjusted as needed. This application specifically uses the polytetrafluoroethylene suspension resin with the brand number MP1600 of DuPont Company of the United States as an example for testing; the tannic acid in the chitosan-derived carbon modified by tannic acid specifically adopts a commercially available product with a CAS number of 1401-55-4 and an effective amount ≥99%, and the chitosan specifically adopts a commercially available product with a CAS number of 1398-61-4 and an effective amount ≥99%; the nano-silicon nitride is specifically a commercially available product that has passed through a 20-mesh sieve and has an effective content ≥99.9%; and the ethanol adopts commercially available anhydrous ethanol.
[0038] The non-stick pan coating prepared in the present application forms a thermal conductive network between the chitosan-derived carbon modified with tannic acid and silicon carbide and is fully dispersed in the non-stick pan coating, so that the non-stick performance of the non-stick pan coating is maintained while further improving the thermal conductivity, uniform heat dissipation and wear resistance of the non-stick pan coating.
[0039] The present application is further described in detail below in conjunction with specific embodiments and comparative examples.
[0040] Example 1
[0041] This embodiment provides a non-stick pan coating, and the preparation method thereof comprises the following steps:
[0042] 1. Preparation of chitosan-derived carbon modified with tannic acid
[0043] (1) Carbonization and degassing: 10 g of chitosan was placed in a tube furnace and heated from room temperature to 800 °C under a nitrogen atmosphere. After cooling to room temperature naturally, the chitosan was degassed under vacuum for 5 h to obtain chitosan-derived carbon.
[0044] (2) Dispersion: 3 g of chitosan-derived carbon was placed in 600 ml of deionized water and ultrasonicated for 5 h to obtain a dispersion;
[0045] (3) Modification: 0.726 g of Tris was added to the dispersion and mixed evenly. The pH was adjusted to 8.5 with HCl solution and 1.5 g of tannic acid was added. The mixture was mixed evenly and reacted for 6 h to obtain a modified solution.
[0046] (4) Centrifugal drying: centrifuge the modified solution, discard the supernatant, add deionized water to the precipitate, centrifuge several times and discard the supernatant until the pH of the supernatant is 7.0, remove the supernatant, collect the precipitate and dry it to obtain the modified powder.
[0047] 2. Preparation of non-stick coating
[0048] (1) Substrate treatment: A non-stick pan substrate with a diameter of 28 cm is subjected to sandblasting roughening treatment to obtain an uneven inner surface of the non-stick pan substrate, and then the inner surface of the non-stick pan substrate is degreased and cleaned to obtain a treated non-stick pan substrate;
[0049] (2) Preliminary stirring: 1.2 g of tannic acid-modified chitosan-derived carbon (hereinafter referred to as “tannic acid-chitosan-derived carbon”), 0.4 g of nano-silicon carbide and 4 g of anhydrous ethanol were weighed and stirred at 2000 rpm for 1 h to obtain a mixed solution;
[0050] (3) Stirring and spraying: adding the mixed solution to 6 g of fluorine-containing resin, stirring and mixing at 2000 rpm for 1 h, and then spray granulating to obtain a powder with a particle size of 1-10 μm;
[0051] (4) Preparing a coating: placing the treated non-stick pan substrate in a vacuum chamber, evacuating the chamber and introducing nitrogen, and then spraying the powder onto the inner surface of the treated non-stick pan substrate by plasma spraying to obtain a non-stick pan coating.
[0052] Embodiment 2-10
[0053] Based on Example 1, the raw material ratio of the non-stick pan coating is adjusted in Example 2-10. The specific adjustment is shown in Table 1.
[0054] Comparative Examples 1-4
[0055] Comparative Examples 1-4 Based on Example 1, the raw material ratio of the non-stick pan coating was adjusted, and the specific adjustment details are shown in Table 1.
[0056] Comparative Example 5
[0057] A non-stick pan with a diameter of 28 cm on the market was selected as a control sample.
[0058] Performance Testing
[0059] 1. Thermal conductivity and uniform heat dissipation performance
[0060] The non-stick pans of Examples 1-10 and Comparative Examples 1-5 were placed on a heating plate set at 260°C, and points 1 to 5 were selected on the inner surface of the non-stick pans of Examples 1-10 and Comparative Examples 1-5. Points 1 to 5 were arranged in sequence on a straight line, with point 3 located at the center of the bottom of the non-stick pan, points 1 and 5 located on the periphery of the bottom of the non-stick pan, point 2 located at the center of the line connecting point 1 and point 3, and point 4 located at the center of the line connecting point 3 and point 5. The temperature of points 1 to 5 was measured using an infrared gun, once per minute for 10 minutes. The average temperature within 10 minutes at each test point was calculated, as shown in Table 2.
[0061] 2. Wear Resistance The non-stick pans of Examples 1-10 and Comparative Examples 1-5 were ground with a grinding wheel for 200 turns under a weight of 250 g according to GB / T 1768-1979, and the weight loss of the coatings was tested. The specific results are shown in Table 3.
[0062] 3. Non-stick performance
[0063] The non-stick pans of Examples 1-10 and Comparative Examples 1-5 were cleaned and placed on a gas stove, and then 2 mL of oil was added, and the mixture was evenly brushed with a silicone brush. Then eggs were added, spread flat, and the non-stick performance of the non-stick pans was evaluated by flipping them with an iron spatula. The specific results are shown in Table 3.
[0064] Table 1 Components of Examples 1-10 and Comparative Examples 1-4
[0065] Fluorine-containing resin / g Tannic acid-chitin derived carbon / g Nano silicon carbide / g Ethanol / g Example 1 6 1.2 0.4 4 Example 2 8 0.45 0.15 6 Example 3 8 1.2 0.4 6 Example 4 6 0.45 0.15 4 Example 5 7 0.9 0.25 5 Example 6 6 1.2 0.3 4 Example 7 6 0.85 0.15 4 Example 8 6 0.8 0.2 4 Example 9 6 0.75 0.25 4 Example 10 6 0.7 0.3 4 Comparative Example 1 5.5 0.45 0.15 3.5 Comparative Example 2 8.5 0.45 0.15 6.5 Comparative Example 3 6 0.4 0.1 4 Comparative Example 4 6 1.3 0.45 4
[0066] Table 2 Test table of thermal conductivity and uniform heat dissipation performance of Examples 1-10 and Comparative Examples 1-5
[0067]
[0068]
[0069] Table 3 Test table of wear resistance and non-stick performance of Examples 1-10 and Comparative Examples 1-5
[0070]
[0071]
[0072] Referring to Tables 1 to 3, it can be seen from the comparison of Examples 1-6 and Comparative Examples 1-5 that as the proportion of tannic acid-chitosan derived carbon and nano-silicon carbide in the non-stick pan coating continues to increase, the heat conduction network formed by tannic acid-chitosan derived carbon and nano-silicon carbide becomes more and more dense, so that the thermal conductivity and uniform heat dissipation performance of the non-stick pan coating continue to increase. However, when the proportion of tannic acid-chitosan derived carbon and nano-silicon carbide in the non-stick pan coating exceeds a certain range, the non-stick performance of the non-stick pan coating is reduced, which may be because tannic acid-chitosan derived carbon and nano-silicon carbide are difficult to disperse evenly in the non-stick pan coating.
[0073] As the share of tannic acid-chitosan derived carbon and nano-silicon carbide in non-stick pan coatings continues to increase, the wear resistance of non-stick pan coatings continues to increase, mainly because both chitosan derived carbon and nano-silicon carbide have excellent wear resistance. After tannic acid-chitosan derived carbon and nano-silicon carbide adhere together through tannic acid to form a network, the wear resistance of the non-stick pan coating is further improved.
[0074] From comparative examples 7-10, it can be seen that when the sum of the proportions of tannic acid-chitosan derived carbon and nano-silicon carbide is the same, as the ratio between tannic acid-chitosan derived carbon and nano-silicon carbide continues to increase, the thermal conductivity, uniform heat dissipation and wear resistance of the non-stick pan coating continue to improve until they tend to stabilize.
[0075] Examples 11-14
[0076] Examples 11-14 are based on Example 1, and the carbonization temperature in step (1) of the method for preparing chitosan-derived carbon modified with tannic acid is adjusted. The specific adjustments are shown in Table 4.
[0077] Comparative Examples 6-7
[0078] Comparative Examples 6-7 Based on Example 1, the carbonization temperature in step (1) of the method for preparing chitosan-derived carbon modified with tannic acid was adjusted. The specific adjustment conditions are shown in Table 4.
[0079] Performance Testing
[0080] The non-stick pan coatings prepared in Examples 11-14 and Comparative Examples 6-7 were tested for thermal conductivity, uniform heat dissipation and non-stick performance as above. The test results are shown in Tables 4 and 5.
[0081] Table 4 Chitosan carbonization temperature data table and non-stick performance test table of Example 1, Examples 11-14 and Comparative Examples 5-7
[0082]
[0083]
[0084] Table 5 Test table of thermal conductivity and uniform heat dissipation performance of Example 1, Examples 11-14 and Comparative Examples 5-7
[0085] Point 1 / ℃ Point 2 / ℃ Point 3 / ℃ Point 4 / ℃ Point 5 / ℃ Example 1 222 234 243 232 224 Embodiment 11 201 217 231 215 202 Example 12 217 233 240 232 218 Embodiment 13 219 232 241 233 217 Embodiment 14 214 226 239 227 213 Comparative Example 5 181 201 219 200 182 Comparative Example 6 170 191 213 192 169 Comparative Example 7 165 187 210 188 166
[0086] Referring to Table 4 and Table 5, it can be seen from the comparison of Example 1, Examples 11-14, and Comparative Examples 5-7 that the thermal conductivity and uniform heat dissipation performance of the non-stick pan coating show a trend of first increasing and then decreasing with the increase of the chitosan carbonization temperature. This may be due to the large amount of gas escape generated by the chitosan oxygen-containing functional groups during the carbonization process, which makes the generated chitosan-derived carbon generate more pore structures, which is conducive to phonon transmission and improves the thermal conductivity and uniform heat dissipation performance of the chitosan-derived carbon. However, when the chitosan carbonization temperature is too high, the pore structure of the generated chitosan-derived carbon may collapse, reducing the thermal conductivity and uniform heat dissipation performance of the chitosan-derived carbon.
[0087] Examples 15-16
[0088] In Examples 15-16, based on Example 1, the amount of tannic acid added in step (3) of the method for preparing chitosan-derived carbon modified with tannic acid was adjusted. The specific adjustments are shown in Table 6.
[0089] Comparative Examples 8-9
[0090] Comparative Examples 8-9 Based on Example 1, the amount of tannic acid added in step (3) of the method for preparing chitosan-derived carbon modified with tannic acid was adjusted. The specific adjustment details are shown in Table 6.
[0091] Performance Testing
[0092] The non-stick pan coatings prepared in Examples 15-16 and Comparative Examples 8-9 were subjected to the above performance tests. The test results are shown in Tables 6 and 7.
[0093] Table 6 Data table of tannic acid addition amount of Example 1, Examples 15-16, Comparative Examples 5 and Comparative Examples 8-9, and test table of wear resistance and non-stick performance
[0094] Tannic acid addition amount / g Coating weight loss / mg Non-stick performance Example 1 1.5 3.5 No egg sticking to the bottom of the pan Embodiment 15 0.5 4.8 No egg sticking to the bottom of the pan Example 16 1 4.4 No egg sticking to the bottom of the pan Comparative Example 5 / 5.0 No egg sticking to the bottom of the pan Comparative Example 8 0.4 5.2 No egg sticking to the bottom of the pan Comparative Example 9 1.6 3.5 No egg sticking to the bottom of the pan
[0095] Table 7 Test table of thermal conductivity and uniform heat dissipation performance of Example 1, Examples 15-16, Comparative Example 5 and Comparative Examples 8-9
[0096] Point 1 / ℃ Point 2 / ℃ Point 3 / ℃ Point 4 / ℃ Point 5 / ℃ Example 1 222 234 243 232 224 Embodiment 15 196 210 224 211 195 Example 16 212 224 235 225 211 Comparative Example 5 181 201 219 200 182 Comparative Example 8 170 193 216 194 171 Comparative Example 9 224 233 243 231 223
[0097] Referring to Table 6 and Table 7, it can be known from Comparative Example 1, Example 15-16, Comparative Example 5 and Comparative Example 8-9 that heat conduction, uniform heat dissipation and wear resistance all show a rising trend as the amount of tannic acid increases. This is because after tannic acid modifies the surface of chitosan-derived carbon, tannic acid-chitosan-derived carbon is fully dispersed in ethanol and fluorine-containing resin. The catechol and pyrogallol structures on the tannic acid are adsorbed on nano-silicon carbide, so that tannic acid-chitosan-derived carbon and nano-silicon carbide form a heat-conducting network, providing a fast channel for phonon transmission, and improving the thermal conductivity and uniform heat dissipation performance of the non-stick pan coating. In addition, due to the good solubility of tannic acid in ethanol and fluorine-containing resin, tannic acid-chitosan-derived carbon and nano-carbon are evenly dispersed as much as possible, thereby improving the wear resistance of the non-stick pan coating.
[0098] Examples 17-19
[0099] In Examples 17-19, based on Example 1, the reaction time in step (3) of the method for preparing chitosan-derived carbon modified with tannic acid was adjusted. The specific adjustments are shown in Table 8.
[0100] Comparative Examples 10-11
[0101] Comparative Examples 10-11 Based on Example 1, the reaction time in step (3) of the method for preparing chitosan-derived carbon modified with tannic acid was adjusted. The specific adjustments are shown in Table 8.
[0102] Performance Testing
[0103] The non-stick pan coatings prepared in Examples 17-19 and Comparative Examples 10-11 were subjected to the above performance tests, and the test results are shown in Tables 8 and 9.
[0104] Table 8 Data table of tannic acid addition amount of Example 1, Examples 17-19, Comparative Examples 5 and Comparative Examples 10-11, and test table of wear resistance and non-stick performance
[0105] Reaction time / h Coating weight loss / mg Non-stick performance Example 1 6 3.5 No egg sticking to the bottom of the pan Embodiment 17 3 4.8 No egg sticking to the bottom of the pan Embodiment 18 4 4.1 No egg sticking to the bottom of the pan Embodiment 19 5 3.7 No egg sticking to the bottom of the pan Comparative Example 5 / 5.0 No egg sticking to the bottom of the pan Comparative Example 10 2.5 5.3 No egg sticking to the bottom of the pan Comparative Example 11 6.5 3.5 No egg sticking to the bottom of the pan
[0106] Table 9 Test table of thermal conductivity and uniform heat dissipation performance of Example 1, Examples 17-19, Comparative Example 5 and Comparative Examples 10-11
[0107] Point 1 / ℃ Point 2 / ℃ Point 3 / ℃ Point 4 / ℃ Point 5 / ℃ Example 1 222 234 243 232 224 Embodiment 17 194 208 224 209 195 Embodiment 18 213 225 235 225 212 Embodiment 19 217 228 239 227 218 Comparative Example 5 181 201 219 200 182 Comparative Example 10 167 188 214 189 167 Comparative Example 11 224 233 243 231 223
[0108] Referring to Table 8 and Table 9, it can be seen from the comparison of Example 1, Examples 17-19, Comparative Example 5 and Comparative Examples 10-11 that the thermal conductivity, uniform heat dissipation and wear resistance all show a rising trend as the reaction time increases. This is because the reaction time continues to increase, and the modification of chitosan-derived carbon by tannic acid is more sufficient, so that more tannic acid is coated on the chitosan-derived carbon, and nano-silicon carbide adheres to the tannic acid, which facilitates the formation of a thermal conductive network by tannic acid-chitosan-derived carbon and nano-silicon carbide, thereby improving the thermal conductivity and uniform heat dissipation of the non-stick pan coating. In addition, more tannic acid makes the tannic acid-chitosan-derived carbon and nano-silicon carbide more evenly dispersed in the non-stick pan coating, thereby improving the wear resistance of the non-stick pan.
[0109] Examples 20-29
[0110] In Examples 20-24, based on Example 1, the stirring rate and stirring time in step (2) of the method for preparing the non-stick pan coating were adjusted. The specific adjustments are shown in Table 10.
[0111] In Examples 25-29, based on Example 1, the stirring rate and stirring time in step (3) of the method for preparing the non-stick pan coating were adjusted. The specific adjustments are shown in Table 10.
[0112] Comparative Examples 12-15
[0113] Comparative Examples 12-13 are based on Example 1, and the stirring rate and stirring time in step (2) of the method for preparing the non-stick pan coating are adjusted. The specific adjustments are shown in Table 10.
[0114] Comparative Examples 14-15 are based on Example 1, and the stirring rate and stirring time in step (3) of the method for preparing the non-stick pan coating are adjusted. The specific adjustments are shown in Table 10.
[0115] Performance Testing
[0116] The non-stick pan coatings prepared in Examples 20-29 and Comparative Examples 12-15 were subjected to the above performance tests. The test results are shown in Tables 11 and 12.
[0117] Table 10 Data table of stirring rates and reaction times in steps (2) and (3) in the preparation of non-stick pan coatings in Example 1, Examples 20-29 and Comparative Examples 12-15
[0118]
[0119] Table 11 Test table of thermal conductivity and uniform heat dissipation performance of Example 1, Examples 20-29, Comparative Example 5 and Comparative Examples 12-15
[0120] Point 1 / ℃ Point 2 / ℃ Point 3 / ℃ Point 4 / ℃ Point 5 / ℃ Example 1 222 234 243 232 224 Embodiment 20 193 207 223 208 194 Embodiment 21 200 214 228 215 199 Embodiment 22 206 218 231 217 207 Embodiment 23 214 225 236 226 215 Embodiment 24 224 233 243 234 223 Embodiment 25 194 206 224 208 193 Embodiment 26 201 213 227 215 200 Embodiment 27 207 217 232 218 206 Embodiment 28 215 224 237 225 216 Embodiment 29 225 234 243 234 223 Comparative Example 5 181 201 219 200 182 Comparative Example 12 178 198 217 197 178 Comparative Example 13 225 233 243 232 224 Comparative Example 14 179 199 217 198 178 Comparative Example 15 224 232 243 233 224
[0121] Table 12 Test table of wear resistance and non-stick performance of Example 1, Examples 20-29, Comparative Example 5 and Comparative Examples 12-15
[0122]
[0123]
[0124] Referring to Tables 10 to 12, in step (2) or step (3), as the rotation speed or time continues to increase, the thermal conductive network formed by the tannic acid-chitosan derived carbon and silicon carbide is more evenly distributed in the non-stick pan coating, and the thermal conductivity, uniform heat dissipation and wear resistance of the non-stick pan coating continue to increase until they stabilize.
[0125] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A non-stick pan coating, characterized in that: The invention comprises the following components by weight: 120-160 parts of fluorine-containing resin, 9-24 parts of chitosan-derived carbon modified by tannic acid, 3-8 parts of nano-silicon carbide, and 80-120 parts of ethanol; the weight ratio of the chitosan-derived carbon modified by tannic acid to the nano-silicon carbide is 3-4:1; The method for preparing the chitosan-derived carbon modified by tannic acid comprises the following steps: (1) Carbonization and degassing: chitosan is placed in a tube furnace and heated from room temperature to 400-1000°C under a nitrogen atmosphere, then naturally cooled to room temperature and degassed under vacuum for 4-6 hours to obtain chitosan-derived carbon; (2) Dispersion: placing the chitosan-derived carbon in deionized water and ultrasonicating for 4-6 hours to obtain a dispersion; (3) Modification: adding Tris to the dispersion and mixing evenly, adjusting the pH to 8-9 with HCl solution, adding tannic acid, mixing evenly and reacting to obtain a modified solution; (4) Centrifugal drying: centrifuge the modified solution, discard the supernatant, add deionized water to the precipitate, centrifuge for multiple times and discard the supernatant until the pH of the supernatant is 7.0, remove the supernatant, collect the precipitate and dry it to obtain the modified powder.
2. The non-stick pan coating according to claim 1, characterized in that: In the step (1), the temperature of the tube furnace is increased to 700-900°C.
3. The non-stick pan coating according to claim 1, characterized in that: The weight ratio of the chitosan-derived carbon to tannic acid in the step (3) is 6:1-3.
4. The non-stick pan coating according to claim 1, characterized in that: The reaction time of the chitosan-derived carbon and the tannic acid in step (3) is 3-6 h.
5. The method for preparing the non-stick pan coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (a) Substrate treatment: The non-stick pan substrate is subjected to sandblasting roughening treatment to obtain an uneven inner surface of the non-stick pan substrate, and then the inner surface of the non-stick pan substrate is degreased and cleaned to obtain a treated non-stick pan substrate; (b) Preliminary stirring: weighing tannic acid-modified chitosan-derived carbon, nano-silicon carbide and ethanol according to weight, and stirring and mixing for a certain period of time to obtain a mixed solution; (c) stirring and spraying: adding the mixed solution to the fluorine-containing resin, stirring and mixing for a certain period of time, and then spraying and granulating to obtain a powder with a particle size of 1-10 μm; (d) Preparing a coating: placing the treated non-stick pan substrate in a vacuum chamber, evacuating the chamber and introducing nitrogen, and then spraying the powder onto the inner surface of the treated non-stick pan substrate by plasma spraying to obtain a non-stick pan coating.
6. The method for preparing a non-stick pan coating according to claim 5, characterized in that: In the step (b), stirring is required at 1000-2000 rpm for 1-2 hours.
7. The method for preparing a non-stick pan coating according to claim 5, characterized in that: In the step (c), stirring is required at 1000-2000 rpm for 1-2 hours.
Citation Information
Patent Citations
High-wear-resistance non-stick coating special for cooker and preparation method thereof
CN108976941A
Magnetic chitin carbonized microsphere adsorbent and preparation method and application thereof
CN111298776A
Preparation method of high-temperature-resistant and wear-resistant non-stick pan coating
CN111808484A